Biomarkers of air pollution exposure--a study of policemen in Prague - Topinka, J; Sevastyanova, O; Binkova, B; Chvatalova, I; Milcova, A; Lnenickova, Z; Novakova, Z; Solansky, I; Sram, R J (Mutation Research-Fundamental and Molecular Mechanisms of Mutagenesis, 2007)
The effect of exposure to organic compounds adsorbed onto respirable air particles (<2.5microm) on DNA adducts in lymphocytes was studied in a group of non-smoking policemen (N=109, aged 35+/-0.9 years) working in the downtown area of Prague and spending >8h daily outdoors. Personal exposure to carcinogenic polycyclic aromatic hydrocarbons (c-PAHs) adsorbed on respirable particles was monitored in each subject for 48h before biological sampling. DNA adducts were analyzed by a (32)P-postlabelling assay, and total DNA adduct levels and B[a]P-like spots were determined. Further biomarkers included cotinine levels in urine to control for exposure to tobacco smoke, plasma levels of vitamins A, E and C and polymorphisms of metabolic genotypes (GSTM1, GSTP1, GSTT1, CYP 1A1-Msp I and Ile/Val, MTHFR, MS), DNA repair genotypes (XRCC1, hOGG1 and XPD exons 6 and 23) and the p53 gene (p53 Msp I and BstU I). All the biomarkers of exposure and effect were analyzed repeatedly during a period of one year at 2-3 month intervals (January, March, June, September 2004) to cover periods with high (winter) and low (summer) levels of air pollution. The highest personal exposure to c-PAHs was found in January (8.1+/-8.8ng/m(3)), while the other three sampling periods exhibited 3-4-fold lower c-PAH exposure. The total DNA adducts were only slightly elevated in January (2.08+/-1.60) compared to March (1.66+/-0.65), June (1.96+/-1.73) and September (1.77+/-1.77). B[a]P-like DNA adducts, however, were significantly higher in January than in the March and June sampling periods (0.26+/-0.14 vs. 0.19+/-0.12 and 0.22+/-0.13, respectively; p<0.0001 and p=0.017) indicating that c-PAH exposure probably plays a crucial role in DNA adduct formation in lymphocytes. No effect of individual metabololic or DNA repair genotypes on DNA adduct levels was observed. However, the combination of two genotypes encoding enzymes metabolizing c-PAHs - CYP 1A1 and GSTM1 - was associated with the levels of total and B[a]P-like DNA adducts under conditions of increased exposure to c-PAHs. Our study suggests that DNA adducts in the lymphocytes of subjects exposed to increased c-PAH levels are an appropriate biomarker of a biologically effective dose, directly indicating whether or not the extent of exposure to these compounds is related to an increased mutagenic and carcinogenic risk.